2012
DOI: 10.3389/fnsys.2012.00008
|View full text |Cite
|
Sign up to set email alerts
|

Network Deficiency Exacerbates Impairment in a Mouse Model of Retinal Degeneration

Abstract: Neural oscillations play an important role in normal brain activity, but also manifest during Parkinson’s disease, epilepsy, and other pathological conditions. The contribution of these aberrant oscillations to the function of the surviving brain remains unclear. In recording from retina in a mouse model of retinal degeneration (RD), we found that the incidence of oscillatory activity varied across different cell classes, evidence that some retinal networks are more affected by functional changes than others. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(111 citation statements)
references
References 49 publications
8
103
0
Order By: Relevance
“…These differences suggest a differential effect of photoreceptor degeneration on the ON and OFF retinal pathways. Published data in the rd1 mouse indicate that a large number of rhythmic NR RGCs have ON morphology (Yee et al 2012). This suggests that in the Tg P23H-1 retina, both pathways likely have rhythmic spontaneous activity as the retina degenerates.…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest a differential effect of photoreceptor degeneration on the ON and OFF retinal pathways. Published data in the rd1 mouse indicate that a large number of rhythmic NR RGCs have ON morphology (Yee et al 2012). This suggests that in the Tg P23H-1 retina, both pathways likely have rhythmic spontaneous activity as the retina degenerates.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after disease onset, alterations to neuronal physiology occur, and oscillatory activity develops in bipolar, amacrine, and ganglion cells (Margolis et al, 2008;Borowska et al, 2011). This aberrant neuronal activity can exacerbate visual impairment, as it obscures signaling from bipolar cells to ganglion cells (Yee et al, 2012). Thus, the loss of photoreceptors is compounded by maladaptive interactions within the inner retinal network, as neuronal oscillations interfere with signal transmission from the retina to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…A possible mechanism is the disruption of a network of gap junction-linked amacrine and bipolar cells, which has been shown to oscillate in wild-type (wt) retina when metabotropic glutamate receptors (mGluRs) are blocked, inducing conditions similar to the loss of photoreceptors (Trenholm et al, 2012). It has been found that blocking gap junction transmission significantly reduces aberrant oscillations (Borowska et al, 2011;Menzler and Zeck, 2011;Yee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, genetically distinct GCs have been categorized morphologically and functionally (see Sanes and Masland, 2015 for a review). Approximately half of mice GCs have been classified in this way and evidence thus far shows a similar pattern to the cat and primate (Sagdullaev & McCall, 2005;van Wyk et al, 2009;Hong et al, 2011, Yee et al, 2012, Sanes and Masland, 2015.…”
Section: Retinal Ganglion Cells Integrate All Retinal Inputs and Provmentioning
confidence: 94%